High risk-myelodysplastic syndrome following CAR T-cell therapy in a patient with relapsed diffuse large B cell lymphoma: A case report and literature review - Accorsi Buttini, Eugenia; Farina, Mirko; Lorenzi, Luisa; Polverelli, Nicola; Radici, Vera; Morello, Enrico; Colnaghi, Federica; Almici, Camillo; Ferrari, Emilio; Bianchetti, Andrea; Leoni, Alessandro; Re, Federica; et al. (Frontiers in Oncology, 2023)
Background Chimeric antigen receptor (CAR) T-cell therapy represents the most advanced immunotherapy against relapsed/refractory B cell malignancies. While cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome are distinctive, known CAR T-cell acute adverse events, hematological toxicity has been increasingly reported. Cytopenia following CAR T-cell treatment is attributed in most cases to lymphodepletion regimens, bridging chemotherapy, or radiotherapy. However, when cytopenia becomes prolonged, the development of myelodysplastic syndrome (MDS) should be considered. Case presentation We report a case of high risk (HR)-MDS following CAR T-cell therapy in a patient with relapsed diffuse large B cell lymphoma. Eight months after CAR T-cell infusion, the blood count showed progressive, worsening cytopenia and the bone marrow biopsy revealed multilineage dysplasia without excess of blasts associated with chromosome 7 deletion and RUNX1 mutation. Next generation sequencing analysis, retrospectively performed on stored samples, showed a germ line CSF3R mutation, CEBPA clonal hematopoiesis, but no RUNX1 lesion. Conclusion We describe a case of HR-MDS, with deletion of chromosome 7 and acquisition of RUNX1 mutation, developing after CAR T-cell therapy in a patient with clonal hematopoiesis (CH). Previous chemotherapy favored MDS onset; however, we could not exclude the fact that the impairment of immunosurveillance related to either lymphodepletion or CAR T-cell infusion may play a role in MDS development. Thus, we designed a multicenter prospective study (ClonHema-CAR-T-Study) to investigate if cytopenia after CAR T-cell treatment may be due to underling CH as well as the presence of secondary myeloid malignancies.